Hadith #2495 - Sunan Abi Dawud - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Alqama bin Mrthd علقمة بن مرثد; Burayda bin al-Husayb; Qa'nab al-Tamimi قعنب التميمي الكوفي; Sa'id bin Mnswr bin Sh'bh سعيد بن منصور بن شعبة; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
Abu Hurairah reported the Apostle of Allaah(ﷺ) as saying “An infidel and the one who killed him will never be brought together in Hell.”
Grade: Sahih

Hadith #2611 - Sunan Abi Dawud - Alqama bin Mrthd علقمة بن مرثد; Burayda bin al-Husayb; Muhammad bin Abi Da'ud al-Bghdady محمد بن أبي داود; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulaiman bin Burayda bin al-Husayb سليمان بن بريدة بن الحصيب; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
The Prophet (ﷺ) said: The best number of companions is four, the best number in expeditions four hundred, and the best number in armies four thousand; and twelve thousand will not be overcome through smallness of numbers. Abu Dawud said: What is correct is that this tradition is mursal (i.e. the link of the Companion is missing).
Grade: Sahih

Hadith #2612 - Sunan Abi Dawud - Alqama bin Mrthd علقمة بن مرثد; Burayda bin al-Husayb; Ibrahim bin Muhammad bin al-Harith إبراهيم بن محمد أبو اسحاق الفزاري; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulaiman bin Burayda bin al-Husayb سليمان بن بريدة بن الحصيب (Sunan Abi Dawud)
Sulaiman bin Buraidah reported on the authority of his father. When the Apostle of Allaah(ﷺ) appointed a Commander over an Army or a detachment, he instructed him to fear Allaah himself and consider the welfare of the Muslims who were with him. He then said “When you meet the polytheists who are your enemy, summon them tone of three things and accept whichever of them they are willing to agree to, and refrain from them. Summon them to Islam and if they agree, accept it from them and refrain
Grade: Sahih

Hadith #4431 - Sunan Abi Dawud - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Alqama bin Mrthd علقمة بن مرثد; Burayda bin al-Husayb; Ghaylan bin Jarir غيلان بن جرير المعولي (Sunan Abi Dawud)
When the Prophet (May peace e upon him) commanded to stone Ma’iz b. Malik, we took him out to Baql. I swear by Allah, we did not tie him, nor did we dig a pit for him. But he was standing before us. The narrator Abu Kamil said: So we threw at him bones, clods of mud and pieces of earthenware. He ran away and we ran after him till he came to a side of the Harrah. He stood there before us and we threw at him big stones of the Harrah until he died. He (the Prophet) did not ask forgiveness for him
Grade: Sahih

Hadith #4695 - Sunan Abi Dawud - Alqama bin Mrthd علقمة بن مرثد; Mhmwd bin Khalid محمود بن خالد; Muhammad bin Yusuf al-Faryabi محمد بن يوسف الفريابي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulaiman bin Burayda bin al-Husayb سليمان بن بريدة بن الحصيب (Sunan Abi Dawud)
The first to speak on Divine decree in al-Basrah was Ma`bad al Juhani. I and Humaid b. `Abd al-Rahman al-Himyari proceeded to perform Hajj or `Umrah. We said : would that we meet any of the Companions of the Messenger of Allah (ﷺ) so that we could ask him about what they say with regard to divine decree. So Allah helped us to meet `Abd Allah b. `Umar who was entering the mosque. So I and my companion surrounded him, and I thought that my companion would entrust me the task of speaking to him.
Grade: Sahih

Hadith #4748 - Sunan Abi Dawud - al-Bara' bin Azib bin al-Harith; Alqama bin Mrthd علقمة بن مرثد; Hisham bin 'Abdul Malik al-Tayalasi هشام بن عبد الملك أبو الوليد الطيالسي; Sa'd bin 'Ubaida al-Salmi سعد بن عبيدة السلمي أبو حمزة; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
When the Prophet of Allah (ﷺ) was lifted to the heavens (for travelling) in Paradise, or as he said, a river whose banks were of transparent or hollowed pearls was presented to him. The angel who was with him struck it with his hand and took out musk. Muhammad (ﷺ) then asked the angel who was with him: What is this? He replied: It is al-Kawthar which Allah has given you.
Grade: Sahih

Hadith #4937 - Sunan Abi Dawud - Alqama bin Mrthd علقمة بن مرثد; Burayda bin al-Husayb; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulaiman bin Burayda bin al-Husayb سليمان بن بريدة بن الحصيب; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
We came to Medina and stayed with Banu al-Harith b. al-Khazraj. She said : I swear by Allah, I was swinging between two date-palms. Then my mother came down; and I had my hair up to the ears. The transmitter then rest of the tradition.
Grade: Hasan Sahih